Prevalence and Associated Factors of Intimate Partner Violence Among Married Women During COVID-19 Pandemic Restrictions: A Community-Based Study - Tadesse, Abay Woday (Journal of interpersonal violence, 2022)
Ethiopia has taken unprecedented preventive measures, such as confinement to home and closure of schools and offices to halt the spread of Corona virus pandemic in the country. Unfortunately, such orders may have been associated with intimate partner violence (IPV) against women but there is no study conducted to assess the magnitude of IPV during the lock-downs in the country. Thus, this study intended to investigate the prevalence and associated factors of IPV against women during the COVID-19 pandemic restrictions. A community-based cross-sectional study was conducted on sample of 617 married or cohabited women. A systematic random sampling technique was employed to identify and enroll women who are married. A logistic regression analysis was used to identify the predictors of IPV among women and all statistical analyses were carried out using STATA 14.2. In this study, amongst the 589 married women who were included in the analysis, 22.4% [95% CI: 19.1%, 25.9%] were experienced at least one form of IPV. Additionally, 11.0%, 20.0%, and 13.8% of women also experienced physical, psychological, and sexual IPVs respectively. After adjusting for covariate; being illiterate [AOR=2.37: 95% CI 1.29, 4.35], having illiterate husband [AOR=2.67: 95% CI 1.36, 5.21], having substance user husband (alcohol, chat or cigarettes) [AOR=2.75: 95% CI 1.42, 5.34], and community tolerant attitude to violence [AOR=2.97: 95% CI 1.17, 7.61] were the independent predictors of IPV amongst married women. In conclusion, the prevalence of IPV among married women was comparable to the national pre-COVID figure of IPV. Therefore, national and regional governments should work toward enhancing gender equality, coupled with addressing risk factors at multiple levels, using community- and institution-based approaches to prevent IPV and to specifically achieve SDG5 of eliminating violence against women by 2030.